Microcontroller-based automatic home gate control system using a remote - Tristianto, Didik; Jarek, Gamaliel K. (International Journal of Business and Information Technology, 2025)
Home security remains a fundamental necessity in modern living. This study presents the design and implementation of an automatic home fence security system based on a microcontroller-controlled remote access mechanism. The system utilizes an ATmega8535 microcontroller, programmed using Code Vision AVR software, to control the opening and closing of the home fence through a password-protected remote keypad. The entered password is verified with the data stored in the system’s memory. Upon successful authentication, the microcontroller activates the L293D motor driver to operate the motor that opens or closes the fence, while an LCD display provides real-time status information. The communication between the transmitter and receiver modules employs infrared (IR) serial communication using the UART protocol to ensure reliable data transfer. Experimental results demonstrate that the proposed system effectively enhances residential security and provides convenient automated control of gate operations.